Quartz raw ore process mineralogy analysis method and method for judging whether quartz raw ore can serve as high-purity quartz raw ore or not

By conducting process mineralogical analysis of quartz raw ore and obtaining its five classification indicators, the problem of the inability to achieve stable production of high-purity quartz sand during the purification of quartz sand in the existing technology is solved, and the efficiency and purity of the stable production of high-purity quartz sand is improved.

CN119534520APending Publication Date: 2025-02-28CHINA BUILDING MATERIALS ACADEMY CO LTD +1
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411854548.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-02-28

Smart Images

  • Figure CN119534520A_ABST
    Figure CN119534520A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of quartz raw ore process mineralogy analysis, and particularly relates to a quartz raw ore process mineralogy analysis method which is a method for judging whether quartz raw ore can be used as high-purity quartz raw ore or not. The quartz raw ore is subjected to sample preparation, wherein a sample preparation method of a powder sample comprises the steps of crushing, wet grinding, filtering concentration and drying in sequence; carrying out chemical component analysis, phase component analysis and crystal structure analysis on the obtained powder sample; and carrying out electron probe microcell analysis, laser Raman spectrum analysis, lithofacies microscopic analysis and inclusion microscopic analysis on the obtained optical sheet. According to the quartz raw ore process mineralogy analysis method, the preparation method of the powder sample is simple, low in energy consumption and environmentally friendly, meanwhile, the obtained powder sample is slightly polluted by the outside, the obtained quartz raw ore process mineralogy analysis result can be closer to a true value, meanwhile, stable production of high-purity quartz sand can be ensured, and the production cost is reduced. And the loss of manpower, financial resources and material resources is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of quartz ore process mineralogy analysis, and specifically relates to a quartz ore process mineralogy analysis method and a method for judging whether quartz ore can be used as high-purity quartz ore. Background Art

[0002] High-purity quartz has excellent physical and chemical properties such as high temperature resistance, corrosion resistance, high strength, high light transmittance, and low thermal expansion coefficient. It is widely used in semiconductors, fiber-optic communications, photovoltaics, optics, electro-light sources and other fields. It is a key basic material for strategic emerging industries such as the new generation of information industry, new energy, high-end equipment, and new materials. It is of great significance to the healthy development of strategic emerging industries.

[0003] High-purity quartz refers to quartz products with SiO2 content > 99.99% after processing, and the impurity element content, inclusion content, hydroxyl content and particle size meet the requirements of semiconductor, photovoltaic, electric light source, optics, communication optical fiber and other related fields. Usually the main impurity element content in high-purity quartz is Al < 30×10 -6 , Ti<10×10 -6 , Li<5×10 -6 , Ca<5×10 -6 , Na<8×10 -6 , K<8×10 -6 , Fe<3×10 -6 , P<2×10 -6 , B<1×10 -6 Mg<3×10 -6 ,Mn<1×10 -6 , Ni<1×10 -6 , Cr<1×10 -6 , Cu<1×10 -6 , Zn<1×10 -6 , Zr<2×10 -6 ,Co<1×10 -6 , and the total content of all impurity elements is less than 100×10 -6 .

[0004] As the high-purity quartz raw material - crystal is increasingly depleted, people are committed to finding natural quartz ores that can replace crystal, such as vein quartz, powder quartz, quartzite, quartz sandstone and granite pegmatite. Natural quartz ore needs to be purified to obtain high-purity quartz sand.

[0005] At present, in the field of quartz sand purification, traditional purification process routes are generally used to directly purify different quartz ores. As a result, due to the types and existence of associated gangue minerals and inclusions in the quartz ores, lattice impurities, etc., it is impossible to achieve stable production of high-purity quartz sand, resulting in a large amount of manpower, financial and material resources. Loss. Summary of the invention

[0006] The purpose of the present invention is to provide a method for technological mineralogical analysis of quartz ore and a method for judging whether quartz ore can be used as high-purity quartz ore. The method for technological mineralogical analysis of quartz ore provided by the present invention is simple, efficient and environmentally friendly. Moreover, by using the technological mineralogical analysis method provided by the present invention to analyze the quartz ore and then purify it, the stable production of high-purity quartz sand can be ensured, and the loss of manpower, financial resources and material resources can be reduced.

[0007] In order to achieve the above object, the present invention provides the following technical solutions:

[0008] The present invention provides a method for process mineralogical analysis of quartz ore, comprising the following steps:

[0009] The quartz ore is sampled to obtain a powder sample and an optical thin slice; the sample preparation method of the powder sample comprises sequentially crushing, wet grinding, filtering, concentrating and drying, and the particle size of the powder sample is d 97 <70μm;

[0010] Conducting chemical composition analysis, phase composition analysis and crystal structure analysis on the powder sample;

[0011] The optical slices were subjected to electron probe microanalysis, laser Raman spectroscopy, petrographic microanalysis and inclusion microanalysis.

[0012] Preferably, the quartz ore includes one or more of vein quartz ore, granite ore and quartzite ore;

[0013] Before the sample preparation, the method further includes: selecting quartz ore with specified characteristics as representative quartz ore; and preparing samples of the representative quartz ore;

[0014] The specified characteristics of the vein quartz ore are: milky white, off-white or white in color, and having an oily luster;

[0015] The specified characteristics of the granite ore are: light flesh-red, light gray or light white in color, and massive granite with a medium-fine grain structure;

[0016] The specified characteristics of the quartzite ore are: blocky quartzite with gray or white color.

[0017] Preferably, the crushing comprises jaw crushing and hammer crushing in sequence; the size of the mineral particles obtained by the jaw crushing is 10-20 mm, and the size of the mineral particles obtained by the hammer crushing is 3-5 mm.

[0018] Preferably, the wet grinding comprises sequentially performing wet coarse grinding and wet fine grinding;

[0019] The particle size of the raw ore slurry obtained by the wet coarse grinding is 97 <300μm;

[0020] The particle size of the raw ore slurry obtained by wet fine grinding is 97 <70μm.

[0021] Preferably, the grinding medium used in the wet rough grinding is a ceramic ball, and the grinding medium of the wet rough grinding includes a first graded grinding medium, a second graded grinding medium and a third graded grinding medium, the particle size of the first graded grinding medium is 10 to 20 mm, the particle size of the second graded grinding medium is 25 to 35 mm, the particle size of the third graded grinding medium is 40 to 50 mm, the mass ratio of the first graded grinding medium, the second graded grinding medium and the third graded grinding medium is (1 to 3): (6 to 8): (1 to 2), the ball-to-material ratio of the wet rough grinding is 4:1 to 5:1; the rotation speed of the wet rough grinding is 800 to 2000 r / min, and the time is 20 to 45 min; the solid content of the wet rough grinding is 30 to 40 wt.%.

[0022] Preferably, the grinding medium used in the wet fine grinding is a ceramic ball, and the grinding medium of the wet fine grinding includes a first graded grinding medium and a second graded grinding medium, the particle size of the first graded grinding medium is 2 to 4 mm, the particle size of the second graded grinding medium is 5 to 6 mm, the mass ratio of the first graded grinding medium to the second graded grinding medium is (3 to 6):1, and the ball-to-material ratio of the wet fine grinding is 4:1 to 5:1; the rotation speed of the wet fine grinding is 1500 to 2500 r / min, and the time is 20 to 30 min; the solid content of the wet fine grinding is 20 to 30 wt.%.

[0023] Preferably, the solid content of the raw ore slurry obtained by filtration and concentration is 65 to 75 wt.%.

[0024] Preferably, the drying is spray drying, the temperature of the spray drying is 100-150° C., and the feed pressure of the spray drying is 0.1-0.2 MPa.

[0025] Preferably, the chemical composition analysis includes: using an X-ray fluorescence spectrometer (XRF) to determine the element content in the ore powder sample, using an inductively coupled plasma mass spectrometer to determine the type and content of the metal elements in the ore powder sample, and using a potassium fluorosilicate volumetric method to determine the SiO2 content in the ore powder sample;

[0026] The phase composition analysis and the crystal structure analysis are performed using an X-ray diffractometer.

[0027] The present invention provides a method for determining whether quartz ore can be used as high-purity quartz ore, comprising the following steps:

[0028] Analyze the quartz ore according to the process mineralogical analysis method described in the above technical solution to obtain five classification indicators of the quartz ore, wherein the five classification indicators include SiO2 content, embedded particle size, gangue mineral type, inclusion characteristics and lattice impurities;

[0029] When at least three of the five classification indicators of the quartz ore reach Grade A or above, the quartz ore can be used as high-purity quartz ore.

[0030] The present invention provides a quartz ore process mineralogical analysis method, comprising the following steps: preparing a sample of the quartz ore to obtain a powder sample and an optical thin slice; the sample preparation method of the powder sample comprises sequentially performing crushing, wet grinding, filtering, concentrating and drying; the particle size d of the powder sample is 97 <70μm; the powder sample is subjected to chemical composition analysis, phase composition analysis and crystal structure analysis; the optical slice is subjected to electron probe micro-area analysis, laser Raman spectroscopy analysis, petrographic microscopic analysis and inclusion microscopic analysis. The quartz ore process mineralogical analysis method provided by the present invention, wherein the preparation method of the powder sample is simple, energy-saving and environmentally friendly, and the obtained powder sample is less polluted by the outside world, so that the obtained quartz ore process mineralogical analysis result can be closer to the true value. The present invention can have an in-depth understanding of the quartz ore through the quartz ore process mineralogical analysis method, facilitate the classification of the quartz ore quality grade and then purify it, ensure the stable production of high-purity quartz sand, and reduce the loss of manpower, financial resources and material resources.

[0031] The present invention provides a method for determining whether quartz ore can be used as high-purity quartz ore, comprising the following steps: analyzing the quartz ore according to the process mineralogy analysis method described in the above technical solution to obtain five classification indicators of the quartz ore, the five classification indicators including SiO2 content, embedded particle size, gangue mineral type, inclusion characteristics and lattice impurities; when at least three of the five classification indicators of the quartz ore reach Grade A or above, the quartz ore can be used as high-purity quartz ore. The method provided by the present invention can ensure the stable production of high-purity quartz sand and reduce the loss of manpower, financial resources and material resources. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 A flowchart of the quartz ore process mineralogical analysis method provided by the present invention;

[0033] Figure 2 This is a picture of the vein quartz ore that needs to be discarded when the vein quartz ore is selected according to color in the present invention;

[0034] Figure 3 This is a picture of the granite ore selected when the granite ore is selected according to color in the present invention;

[0035] Figure 4 This is a picture of the quartzite ore selected when the quartzite ore is selected according to color in the present invention;

[0036] Figure 5 This is an optical picture of inclusions in the vein quartz ore obtained in Example 1 of the present invention;

[0037] Figure 6 This is an optical picture of inclusions in the granite ore obtained in Example 2 of the present invention;

[0038] Figure 7 This is an optical picture of inclusions in the quartzite ore obtained in Example 3 of the present invention. DETAILED DESCRIPTION

[0039] The present invention provides a method for process mineralogical analysis of quartz ore, comprising the following steps:

[0040] The quartz ore is sampled to obtain a powder sample and an optical thin slice; the sample preparation method of the powder sample comprises sequentially crushing, wet grinding, filtering, concentrating and drying, and the particle size of the powder sample is d 97 <70μm;

[0041] Conducting chemical composition analysis, phase composition analysis and crystal structure analysis on the powder sample;

[0042] The optical slices were subjected to electron probe microanalysis, laser Raman spectroscopy, petrographic microanalysis and inclusion microanalysis.

[0043] In the present invention, unless otherwise specified, all preparation raw materials / components are commercially available products well known to those skilled in the art.

[0044] The present invention prepares samples of the quartz ore to obtain powder samples and optical slices. In the present invention, the quartz ore preferably includes one or more of vein quartz ore, granite ore and quartzite ore. Before the sample preparation, the present invention preferably also includes: selecting quartz ore with specified characteristics as a representative quartz ore; and preparing samples of the representative quartz ore. In the present invention, when the quartz ore is preferably vein quartz ore, the specified characteristics of the vein quartz ore are preferably: the color is milky white, off-white or white, and has an oily luster. The present invention preferably also includes: selecting vein quartz ore with a color of milky white, off-white or white and an oily luster as a representative quartz ore, such as vein quartz ore with yellow, black, brown impurities on the surface, and not selecting; if Figure 2 The quartz ore is a discarded vein quartz ore. When the quartz ore is preferably a granite ore, the specified characteristics of the granite ore are preferably: a block granite with a light flesh-red, light gray or light white color and a medium-fine grain structure. The present invention preferably also includes: selecting a block granite with a light flesh-red, light gray, light white color and a medium-fine grain structure as a representative quartz ore, and discarding a coarse grain structure ore with a light flesh-red, light gray, light white, light green, yellow, etc. color; such as Figure 3 The quartz ore is preferably a quartzite ore, and the specified characteristics of the quartzite ore are preferably: gray or white block quartzite. The present invention preferably also includes: using gray or white block quartzite as a representative quartz ore, such as Figure 4 The selected quartzite ore.

[0045] In the present invention, the powder sample preparation method comprises sequentially crushing, wet grinding, filtering, concentrating and drying, and the particle size d of the powder sample is 97 <70μm.

[0046] In the present invention, the crushing preferably includes jaw crushing and hammer crushing in sequence. The size of the mineral particles obtained by the jaw crushing is preferably 10 to 20 mm. The size of the mineral particles obtained by the hammer crushing is preferably 3 to 5 mm.

[0047] In the present invention, the wet grinding preferably includes wet coarse grinding and wet fine grinding in sequence. The particle size d of the raw ore slurry obtained by the wet coarse grinding is 97 Preferably <300 μm. The particle size d of the raw ore slurry obtained by wet fine grinding 97 Preferably <70 μm.

[0048] In the present invention, the wet rough grinding is preferably carried out in a wet grinder. The grinding media used in the wet rough grinding is preferably ceramic balls, specifically Al2O3 ceramic balls and / or ZrO2 ceramic balls. The grinding media of the wet rough grinding preferably include a first graded grinding medium, a second graded grinding medium and a third graded grinding medium, the particle size of the first graded grinding medium is preferably 10 to 20 mm, and can be 15 mm in the embodiment, the particle size of the second graded grinding medium is preferably 25 to 35 mm, and can be 30 mm in the embodiment, the particle size of the third graded grinding medium is preferably 40 to 50 mm, and can be 45 mm in the embodiment, the mass ratio of the first graded grinding medium, the second graded grinding medium and the third graded grinding medium is preferably (1 to 3): (6 to 8): (1 to 2), and can be 2:7:1 in the embodiment. The solvent used in the wet ball milling is preferably water, and in the embodiment it is specifically deionized water. The ball-to-material ratio of the wet rough grinding is preferably 4:1-5:1; the rotation speed of the wet rough grinding is preferably 800-2000r / min, more preferably 1000-1500r / min; the time of the wet rough grinding is preferably 20-45min, more preferably 25-35min. The solid content of the wet rough grinding is preferably 30-40wt.%. The present invention preferably places the wet rough grinding material in a ball mill for grinding, and during the wet rough grinding, the total volume of the wet rough grinding material accounts for 55-65% of the volume of the ball mill. The wet rough grinding material includes the crushed raw ore particles, water and rough grinding grinding media.

[0049] In the present invention, the wet fine grinding is preferably carried out in a horizontal sand mill. The wet coarse grinding obtains a coarse grinding slurry. In the present invention, the coarse grinding slurry is preferably diluted with water before the wet fine grinding. The dilution water is preferably deionized water, and the solid content of the slurry obtained after the dilution is preferably 20 to 30 wt.%. The grinding media used in the wet fine grinding is preferably ceramic balls, specifically Al2O3 ceramic balls and / or ZrO2 ceramic balls. The grinding media of the wet fine grinding preferably include a first graded grinding media and a second graded grinding media, the particle size of the first graded grinding media is preferably 2-4 mm, and can be 3 mm in the embodiment, the particle size of the second graded grinding media is preferably 5-6 mm, the mass ratio of the first graded grinding media to the second graded grinding media is preferably (3-6):1, and can be 4:1 in the embodiment, and the ball-to-material ratio of the wet fine grinding is preferably 4:1-5:1; the rotation speed of the wet fine grinding is preferably 1500-2500 r / min, more preferably 1800-2000 r / min; the time of the wet fine grinding is preferably 20-30 min; the solid content of the wet fine grinding is preferably 20-30 wt.%. The present invention preferably places the wet fine grinding material in a ball mill for grinding, and during the wet fine grinding, the total volume of the wet fine grinding material accounts for 60-75% of the volume of the ball mill. The wet fine grinding material includes the coarse grinding slurry obtained by wet coarse grinding, dilution water and fine grinding grinding media.

[0050] In the present invention, the solid content of the raw ore slurry obtained by filtration and concentration is preferably 65 to 75 wt.%.

[0051] In the present invention, the drying is preferably spray drying, the temperature of the spray drying is preferably 100 to 150° C., and the feed pressure of the spray drying is preferably 0.1 to 0.2 MPa.

[0052] In the present invention, the particle size d of the powder sample obtained by drying is 97 <70μm.

[0053] The powder sample preparation method provided by the present invention preferably comprises the following steps in sequence: jaw crusher → hammer crusher → wet grinding → filtration concentration → spray drying. The powder sample preparation method provided by the present invention is simple, efficient and environmentally friendly.

[0054] The present invention preferably uses representative quartz ore to prepare optical thin slices, and the size of the sample preparation material used for the optical thin slices is preferably 25mm×25mm×5mm. The number of the optical thin slices is preferably 3.

[0055] In the present invention, the optical thin film sample preparation method preferably includes the following steps in sequence: gluing → surface grinding and polishing → bonding and fixing → vacuum drying → thin film cutting → grinding and polishing to a thin film thickness of ≤0.03 mm → covering.

[0056] In the present invention, the thickness of the optical sheet is ≤0.03 mm.

[0057] After obtaining the powder sample, the present invention performs chemical composition analysis, phase composition analysis and crystal structure analysis on the powder sample.

[0058] In the present invention, the chemical composition analysis preferably includes: using an X-ray fluorescence spectrometer (XRF) to determine the element content in the ore powder sample; using an inductively coupled plasma mass spectrometer to determine the type and content of the metal elements in the ore powder sample. Using potassium fluorosilicate volumetric method to determine the SiO2 content in the ore powder sample.

[0059] In the present invention, the phase composition analysis and the crystal structure analysis are performed using an X-ray diffractometer. The phase composition analysis and the crystal structure analysis preferably include: using an X-ray powder diffractometer to qualitatively analyze the phase composition, unit cell parameters and crystal structure of the quartz ore.

[0060] After obtaining the optical thin slice, the present invention performs electron probe micro-area analysis, laser Raman spectrum analysis, petrographic microscopic analysis and inclusion microscopic analysis on the optical thin slice.

[0061] In the present invention, the petrographic microscopic analysis and inclusion microscopic analysis preferably include: using a transmission polarized light or reflection polarized light microscope to observe the aggregation state of quartz crystals, particle size and distribution, distribution of mineral inclusions and gas-liquid inclusions, etc.

[0062] The electron probe micro-area analysis preferably includes: using an electron probe to perform micro-area analysis on the quartz ore slice, combining a polarizing microscope and an X-ray powder diffractometer to identify the mineral phases. Rapidly and accurately identify the composition and content of the minerals in the micro-area; perform point, line and surface scanning analysis on the optical slice, and study and analyze the inclusions, impurity element composition and content inside the quartz crystal.

[0063] The laser Raman spectroscopy analysis preferably includes: using a laser Raman spectrometer to perform inclusion phase and composition analysis on an optical slice, qualitatively and quantitatively analyzing the gas phase, liquid phase and even solid phase contained in a single inclusion, and judging the primary inclusions and secondary inclusions in the original ore. In the present invention, the laser Raman spectroscopy analysis meets the requirements for mineral inclusion composition analysis, and can not only perform single inclusion composition analysis on primary inclusions and secondary inclusions respectively, but also qualitatively and quantitatively analyze the gas phase, liquid phase and even solid phase (if it contains daughter minerals) contained in a single inclusion at the same time.

[0064] The process mineralogical analysis method for quartz ore provided by the present invention classifies the quartz ore based on the test results obtained by the process mineralogical analysis method, and conducts chemical purification test research on the quartz ore, and finally determines the quartz ore that can produce 4N8 grade high-purity quartz.

[0065] The process mineralogical analysis method for quartz ore provided by the present invention can provide an in-depth understanding of the types and existence modes of associated gangue minerals and inclusions, lattice impurities, etc. in the quartz ore, and can classify the quartz ore according to indicators such as SiO2 content, embedded particle size, gangue mineral types, inclusion characteristics and lattice impurities in the ore. If three of the above five indicators of the quartz ore reach Grade A or above, it can be recommended as a high-purity quartz raw material.

[0066] The present invention provides a method for determining whether quartz ore can be used as high-purity quartz ore, comprising the following steps:

[0067] Analyze the quartz ore according to the process mineralogical analysis method described in the above technical solution to obtain five classification indicators of the quartz ore, wherein the five classification indicators include SiO2 content, embedded particle size, gangue mineral type, inclusion characteristics and lattice impurities;

[0068] When at least three of the five classification indicators of the quartz ore reach Grade A or above, the quartz ore can be used as high-purity quartz ore.

[0069] In the present invention, the production process of producing high-purity quartz from granite ore preferably includes the following steps in sequence: crushing → grinding → screening → magnetic separation → flotation → drying → calcination and water quenching → filtration → drying → primary acid leaching → washing → filtration → drying → secondary acid leaching → washing → filtration → drying.

[0070] In order to further illustrate the present invention, the technical solutions provided by the present invention are described in detail below in conjunction with embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0071] The following examples are all based on Figure 1 The flow chart of the quartz ore process mineralogical analysis method is shown in the figure.

[0072] Example 1

[0073] This embodiment provides a vein quartz ore process mineralogy analysis method, which specifically includes the following steps:

[0074] First, a representative vein quartz ore 2 is selected from the vein quartz ore 1. The selection criteria for the vein quartz ore are as follows: vein quartz ore with milky white, grayish white or white color and oily luster is selected. Vein quartz ore with yellow, black or brown impurities on the surface is not selected; Figure 2 It is the discarded vein quartz ore.

[0075] A representative vein quartz ore 2 was scribed, and three small samples with a size of 25 mm×25 mm×5 mm were cut from the representative vein quartz ore 2 using a cutting machine, namely, small sample 3-1, small sample 3-2 and small sample 3-3.

[0076] All the vein quartz ores 4 except the small pieces of samples 3-1, 3-2 and 3-3 were crushed by jaw crushing to vein quartz ores 5 with mineral particle sizes of 10 mm to 20 mm.

[0077] The vein quartz ore 5 is then hammer-broken to produce vein quartz ore 6 with a mineral particle size of 3 mm to 5 mm.

[0078] The vein quartz ore 6 is placed in a grinding jar with a volume of 5L for wet grinding. The filling rate of the grinding jar is 60%. The grinding medium is zirconium oxide. The ratio of zirconium oxide balls is Φ(10mm):Φ(35mm):Φ(45mm)=2:7:1. The vein quartz ore 6 and deionized water are placed in a mass ratio of 4:1 ball-to-material ratio and 3:2 water-to-material ratio. Then, the grinding is started. The grinding speed is 1500r / min and the grinding time is 30min. The obtained quartz powder particle size distribution is: d 10 =64.67μm, d 50 =113.90μm, d 90 =210.50μm, d 97 =288.90 μm, the sample particle size meets the expected requirements, and vein quartz ore slurry 7 is obtained.

[0079] After the vein quartz ore slurry 7 was diluted to a concentration of 25wt.%, the sample was placed in a horizontal sand mill with a grinding jar volume of 3L for fine grinding. The filling rate of the grinding jar was 65%, the grinding medium was zirconium oxide, and the ratio of zirconium oxide balls was Φ(4mm):Φ(6mm)=4:1. The vein quartz ore slurry 7 was placed in a ratio of balls to materials of 4:1, and then the grinding was started. The grinding speed was 2000r / min and the grinding time was 25min. The obtained quartz powder particle size distribution was: d 10 =11.27μm, d 50 =25.38μm, d 90 =61.97μm, d 97 =68.90 μm, the sample particle size meets the expected requirements, and vein quartz ore slurry 8 is obtained.

[0080] The vein quartz raw ore slurry 8 was filtered and concentrated to a concentration of 65% to obtain the vein quartz raw ore slurry 9.

[0081] The vein quartz ore slurry 9 is spray dried (drying temperature is 110°C, feed pressure is 0.2MPa) to obtain vein quartz ore powder 10 of qualified particle size, and then the vein quartz ore powder 10 is subjected to chemical composition detection and phase and crystal structure analysis, the element content is determined by XRF, the metal elements are determined by inductively coupled plasma mass spectrometry, and the SiO2 content in the ore is determined by potassium fluorosilicate volumetric method.

[0082] The vein quartz ore powder 10 is subjected to phase composition and crystal structure analysis using an X-ray diffractometer. Combined with the chemical composition analysis results, the mineral composition and SiO2 content in the vein quartz ore can be preliminarily determined.

[0083] The small piece of sample 3-1 is prepared into an optical thin sheet 11 according to the sample preparation process of gluing → grinding and polishing the mineral surface → bonding and fixing → vacuum drying → cutting into thin slices → grinding and polishing to the thickness of the thin slice ≤ 0.03 mm → cover sheet.

[0084] The optical slice 11 is placed under a polarizing microscope to observe the aggregation state of inclusions, particle size and distribution, distribution of mineral inclusions and gas-liquid inclusions, etc.

[0085] The small samples 3-2 and 3-3 were prepared into optical thin sheets 12 and 13 respectively according to the sample preparation process of gluing → grinding and polishing the mineral surface → bonding and fixing → vacuum drying → cutting thin sheets → grinding and polishing to the thin sheet thickness ≤ 0.03 mm.

[0086] An electron probe is used to perform micro-area analysis on the optical thin slice 12, and combined with an X-ray powder diffractometer and a polarizing microscope to identify the mineral phase, the composition and content of the minerals in the micro-area can be quickly and accurately identified, and the thin slice is scanned and analyzed by point, line, and surface, so as to study and analyze the internal inclusions, impurity element composition, and content of the quartz crystal.

[0087] Laser Raman spectrometer is used to analyze the phase and composition of inclusions in the optical slice 13, and qualitative and quantitative analysis is performed on the gas phase, liquid phase and even solid phase contained in a single inclusion to determine the primary inclusions and secondary inclusions in the original ore.

[0088] Through the process mineralogical analysis of the vein quartz ore, it is known that its main component is quartz, and other impurity minerals are mainly feldspar, hematite, and dolomite. Table 1 shows the chemical composition analysis results. The size and distribution of inclusions in the vein quartz ore: small inclusions are distributed in a beaded shape, with a particle size of less than 2μm, and the beading direction is relatively regular; larger inclusions are irregular, polygonal, and round, and are produced with small beaded inclusions or produced alone, with gas-liquid two phases, and the gas phase content is about 50% (such as Figure 5 shown).

[0089] The vein quartz was purified according to the purification process of crushing → calcination and water quenching → crushing → screening → primary acid leaching → washing → filtration → drying → secondary acid leaching → washing → filtration → drying. The metal impurity content of the purified sample is shown in Table 2. The total amount of impurities is 173.57 ppm. The purity of the purified quartz is greater than 99.98%, among which the content of aluminum and alkali metals is relatively high. Part of the aluminum is a lattice impurity and is difficult to remove. In the later stage, flotation and high-temperature chlorination processes can be considered to purify the vein quartz sample to further improve the purity of the sample.

[0090] Table 1 Chemical composition analysis results of vein quartz ore (unit: g / g, %)

[0091] <![CDATA[SiO2]]> <![CDATA[Al2O3]]> <![CDATA[Fe2O3]]> CaO <![CDATA[K2O]]> MgO NaO <![CDATA[TiO2]]> LOI Total 99.26 0.48 0.03 <0.01 0.11 <0.01 0.01 <0.05 0.10 99.99

[0092] Table 2 Metal impurity content of the vein quartz ore after purification (unit: μg / g, ppm)

[0093] Li Na Mg K Ca Ti Cr Mn Fe Co Ni Cu Al B Total impurities content 4.2 27.4 0.64 18.2 6.92 6.51 0 0.42 3.08 0 0 0.07 106.1 0.03 173.57

[0094] Example 2

[0095] This embodiment provides a method for process mineralogy analysis of granite ore, which specifically includes the following steps:

[0096] Firstly, a representative granite ore 2 is selected from the granite ore 1. The selection criteria of the granite ore are as follows: blocky granites with light flesh-red, light gray, light white and medium-fine grain structure are selected as the research object, and the ores with light flesh-red, light gray, light white, light green, yellow and coarse grain structure are discarded; Figure 3 For the selected granite ore.

[0097] A representative granite ore 2 was scribed, and three small samples with a size of 25 mm×25 mm×5 mm were cut from the representative granite ore 2 using a cutting machine, namely, small sample 3-1, small sample 3-2 and small sample 3-3.

[0098] All the granite ores 4 except the small pieces of samples 3-1, 3-2 and 3-3 were crushed by jaw crushing to granite ores 5 with a mineral particle size of 10 mm to 15 mm.

[0099] The granite ore 5 is then hammer-broken to be crushed into granite ore 6 with a mineral particle size of 2 mm to 3 mm.

[0100] The granite ore 6 was placed in a grinding jar with a volume of 5L for wet grinding. The filling rate of the grinding jar was 60%. The grinding medium was zirconium oxide. The ratio of zirconium oxide balls was Φ(10mm):Φ(30mm):Φ(40mm)=2:7:1. The granite ore 6 and deionized water were placed in a ratio of 5:1 between balls and materials and 7:3 between water and materials. The grinding was then started. The grinding speed was 1500r / min and the grinding time was 25min. The particle size distribution of the obtained quartz powder was: d 10 =58.26μm, d 50 =129.70μm, d 90 =230.60μm, d 97 =292.40 μm, the sample particle size meets the expected requirements, and granite ore slurry 7 is obtained.

[0101] After the granite ore slurry 7 was diluted to a concentration of 25wt.%, the sample was placed in a horizontal sand mill with a grinding jar volume of 3L for fine grinding. The filling rate of the grinding jar was 65%, the grinding medium was zirconium oxide, and the ratio of zirconium oxide balls was Φ(3mm):Φ(5mm)=4:1. The granite ore slurry 7 was placed in a ratio of 5:1, and then the grinding was started. The grinding speed was 2000r / min and the grinding time was 20min. The obtained quartz powder particle size distribution was: d 10 =9.18μm, d 50 =21.46μm, d 90 =56.45μm, d 97 =67.71 μm, the sample particle size meets the expected requirements, and granite ore slurry 8 is obtained.

[0102] The granite ore slurry 8 was filtered and concentrated to a concentration of 65% to obtain a granite ore slurry 9.

[0103] The granite ore slurry 9 is spray dried (drying temperature is 110° C., feed pressure is 0.2 MPa) to obtain granite ore powder 10 of qualified particle size, and then the granite ore powder 10 is subjected to chemical composition detection and phase and crystal structure analysis, the element content is determined using XRF, the metal elements are determined using inductively coupled plasma mass spectrometry, and the SiO2 content in the ore is determined using potassium fluorosilicate volumetric method.

[0104] The phase composition and crystal structure of the granite ore powder 10 are analyzed by using an X-ray diffractometer. Combined with the chemical composition analysis results, the mineral composition and SiO2 content in the granite ore can be preliminarily determined.

[0105] The small piece of sample 3-1 is prepared into an optical thin sheet 11 according to the sample preparation process of gluing → grinding and polishing the mineral surface → bonding and fixing → vacuum drying → cutting into thin slices → grinding and polishing to the thickness of the thin slice ≤ 0.03 mm → cover sheet.

[0106] The optical slice 11 is placed under a polarizing microscope to observe the aggregation state of inclusions, particle size and distribution, distribution of mineral inclusions and gas-liquid inclusions, etc.

[0107] The small samples 3-2 and 3-3 were prepared into optical thin sheets 12 and 13 respectively according to the sample preparation process of gluing → grinding and polishing the mineral surface → bonding and fixing → vacuum drying → cutting thin sheets → grinding and polishing to the thin sheet thickness ≤ 0.03 mm.

[0108] An electron probe is used to perform micro-area analysis on the optical thin slice 12, and combined with an X-ray powder diffractometer and a polarizing microscope to identify the mineral phase, the composition and content of the minerals in the micro-area can be quickly and accurately identified, and the thin slice is scanned and analyzed by point, line, and surface, so as to study and analyze the internal inclusions, impurity element composition, and content of the quartz crystal.

[0109] Laser Raman spectrometer is used to analyze the phase and composition of inclusions in the optical slice 13, and qualitative and quantitative analysis is performed on the gas phase, liquid phase and even solid phase contained in a single inclusion to determine the primary inclusions and secondary inclusions in the original ore.

[0110] Through the process mineralogy research and analysis of the granite ore, it is known that its main minerals are plagioclase and quartz, and it also contains a certain amount of potassium feldspar, muscovite and biotite, hematite and magnetite, and a very small amount of apatite. Table 3 shows the chemical composition analysis results. The types, sizes and distribution of inclusions in the granite: small inclusions are mostly produced in the form of beads, with a particle size of less than 2μm, gas-liquid two phases; inclusions with a particle size of 5-10μm are produced alone or in groups, with irregular, polygonal, rounded, sub-rounded, gas-liquid two phases, and a gas phase content of 40%-70% (such as Figure 6 The quartz particles contain a small amount of solid inclusions, the particle size of the inclusions is small, most of them are 2 to 5 μm, and some of them are larger, with a particle size of 10 to 15 μm.

[0111] The granite ore was purified according to the purification process of crushing → grinding → screening → magnetic separation → flotation → drying → calcination and water quenching → filtration → drying → primary acid leaching → washing → filtration → drying → secondary acid leaching → washing → filtration → drying. The metal impurity content of the purified sample is shown in Table 4. The total amount of impurities is 13.73ppm. The purity of the purified sample is greater than 99.998%, among which the contents of calcium and sodium are relatively high. The sample can be purified by a high-temperature chlorination process in the later stage to further improve the purity.

[0112] Table 3 Chemical composition analysis results of granite ore (unit: g / g, %)

[0113] <![CDATA[SiO2]]> <![CDATA[Al2O3]]> <![CDATA[Fe2O3]]> FeO CaO MgO <![CDATA[K2O]]> MnO NaO <![CDATA[TiO2]]> <![CDATA[P2O5]]> ZnO LOI Total 66.85 16.78 1.65 0.84 0.06 <0.01 11.20 <0.01 2.16 <0.01 0.07 <0.01 0.38 99.99

[0114] Table 4 Metal impurity content of granite ore after purification (unit: μg / g, ppm)

[0115] Li Na Mg K Ca Ti Cr Mn Fe Co Ni Cu Al B Total impurities content 0.45 2.73 0.04 0.53 1.52 <0.01 0 0.04 0.25 <0.01 0.02 0.03 8.03 0.09 13.73

[0116] Example 3

[0117] This embodiment provides a quartzite ore process mineralogy analysis method, which specifically includes the following steps:

[0118] First, a representative quartzite ore 2 is selected from the quartzite ore 1. The selection criteria for the quartzite ore are: The selection criteria for quartzite: Gray and white blocky quartzite is taken as the research object, such as Figure 4 The selected quartzite ore.

[0119] A representative quartzite ore 2 was scribed, and three small samples with a size of 25 mm×25 mm×5 mm were cut from the representative quartzite ore 2 using a cutting machine, namely, small sample 3-1, small sample 3-2 and small sample 3-3.

[0120] All quartzite ores 4 except small pieces of samples 3-1, 3-2 and 3-3 were crushed by jaw crushing to quartzite ores 5 with a mineral particle size of 10 mm to 15 mm.

[0121] The quartzite ore 5 is then hammer-broken to produce quartzite ore 6 with a mineral particle size of 2 mm to 3 mm.

[0122] The quartzite ore 6 was placed in a grinding jar with a volume of 5L for wet grinding. The filling rate of the grinding jar was 60%. The grinding medium was zirconium oxide. The ratio of zirconium oxide balls was Φ(15mm):Φ(35mm):Φ(50mm)=2:7:1. The quartzite ore 6 and deionized water were placed in a ratio of 4:1 between balls and materials and 3:2 between water and materials. The grinding was then started. The grinding speed was 1500r / min and the grinding time was 25min. The obtained quartz powder had a particle size distribution of: d 10 =56.31μm, d 50 =117.40μm, d 90 =215.70μm, d 97 =289.80 μm, the sample particle size meets the expected requirements, and quartzite ore slurry 7 is obtained.

[0123] After the quartzite ore slurry 7 was diluted to a concentration of 25wt.%, the sample was placed in a horizontal sand mill with a grinding jar volume of 3L for fine grinding. The filling rate of the grinding jar was 65%, the grinding medium was zirconium oxide, and the ratio of zirconium oxide balls was Φ(4mm):Φ(6mm)=4:1. The quartzite ore slurry 7 was placed in a ratio of 4:1 between balls and materials, and then the grinding was started. The grinding speed was 2000r / min and the grinding time was 25min. The obtained quartz powder particle size distribution was: d 10 =7.12μm, d 50 =25.67μm, d 90 =54.78μm, d 97 =69.17 μm, the sample particle size meets the expected requirements, and quartzite ore slurry 8 is obtained.

[0124] The quartzite ore slurry 8 is filtered and concentrated to a concentration of 65% to obtain the quartzite ore slurry 9.

[0125] The quartzite ore slurry 9 is spray dried (drying temperature is 110°C, feed pressure is 0.2MPa) to obtain quartzite ore powder 10 of qualified particle size, and then the quartzite ore powder 10 is subjected to chemical composition detection and phase and crystal structure analysis, the element content is determined by XRF, the metal elements are determined by inductively coupled plasma mass spectrometry, and the SiO2 content in the ore is determined by potassium fluorosilicate volumetric method.

[0126] The phase composition and crystal structure analysis of the quartzite ore powder 10 is performed using an X-ray diffractometer. Combined with the chemical composition analysis results, the mineral composition and SiO2 content in the quartzite ore can be preliminarily determined.

[0127] The small piece of sample 3-1 is prepared into an optical thin sheet 11 according to the sample preparation process of gluing → grinding and polishing the mineral surface → bonding and fixing → vacuum drying → cutting into thin slices → grinding and polishing to the thickness of the thin slice ≤ 0.03 mm → cover sheet.

[0128] The optical slice 11 is placed under a polarizing microscope to observe the aggregation state of inclusions, particle size and distribution, distribution of mineral inclusions and gas-liquid inclusions, etc.

[0129] The small samples 3-2 and 3-3 were prepared into optical thin sheets 12 and 13 respectively according to the sample preparation process of gluing → grinding and polishing the mineral surface → bonding and fixing → vacuum drying → cutting thin sheets → grinding and polishing to the thin sheet thickness ≤ 0.03 mm.

[0130] An electron probe is used to perform micro-area analysis on the optical thin slice 12, and combined with an X-ray powder diffractometer and a polarizing microscope to identify the mineral phase, the composition and content of the minerals in the micro-area can be quickly and accurately identified, and the thin slice is scanned and analyzed by point, line, and surface, so as to study and analyze the internal inclusions, impurity element composition, and content of the quartz crystal.

[0131] Laser Raman spectrometer is used to analyze the phase and composition of inclusions in the optical slice 13, and qualitative and quantitative analysis is performed on the gas phase, liquid phase and even solid phase contained in a single inclusion to determine the primary inclusions and secondary inclusions in the original ore.

[0132] Through the process mineralogy research and analysis of the quartzite ore, it is known that the main component of quartzite is quartz, and the impurity minerals are mainly mica, potassium feldspar, sodium feldspar, and hematite. Table 5 shows the chemical composition analysis results. The size and distribution of inclusions in the quartzite: the inclusions are distributed in clusters, which are relatively dense. The large ones are oblong and irregular, with a particle size of 5 to 15 μm, gas-liquid two phases, and the gas phase content is 40% to 60% (such as Figure 7 shown).

[0133] The quartzite ore was purified according to the purification process of crushing → calcination and water quenching → crushing → screening → magnetic separation → flotation → washing → filtration → drying → primary acid leaching → washing → filtration → drying → secondary acid leaching → washing → filtration → drying. The metal impurity content of the purified sample is shown in Table 6. The total impurity amount is 34.82ppm. The purity of the purified quartz is greater than 99.996%, among which the aluminum and alkali metal contents are relatively high. Part of the aluminum is a lattice impurity, which is difficult to remove. K and Na exist in the lattice gap as compensating ions. In the later stage, it can be considered to purify the quartzite by changing the acid washing system and high-temperature chlorination, so as to further improve its purity.

[0134] Table 5 Chemical composition analysis results of quartzite ore (unit: g / g, %)

[0135] <![CDATA[SiO2]]> <![CDATA[Al2O3]]> <![CDATA[Fe2O3]]> CaO <![CDATA[Li2O]]> <![CDATA[K2O]]> MgO NaO <![CDATA[TiO2]]> LOI Total 91.88 2.53 3.47 <0.01 0.11 1.25 <0.01 0.54 <0.01 0.21 99.99

[0136] Table 6: Metal impurity content of the quartzite after purification (unit: μg / g, ppm)

[0137] Li Na Mg K Ca Ti Cr Mn Fe Co Ni Cu Al B Total impurities content 0.20 3.28 0.84 1.64 1.14 1.90 0.04 0.01 0.50 0 0 0.1 25.15 0.02 34.82

[0138] From the above examples, it can be seen that the quartz ore process mineralogy analysis method provided by the present invention, wherein the preparation method of the powder sample is simple, low in energy consumption, and environmentally friendly, and the obtained powder sample is less polluted by the outside world, and the obtained quartz ore process mineralogy analysis result can be closer to the true value. The present invention can have an in-depth understanding of the quartz ore through the quartz ore process mineralogy analysis method, which is convenient for dividing the quartz ore quality grade and then purifying it, and can ensure the stable production of high-purity quartz sand and reduce the loss of manpower, financial resources and material resources.

[0139] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A method for process mineralogy analysis of quartz ore, characterized in that: The following steps are involved: The quartz ore is sampled to obtain a powder sample and an optical thin slice; the sample preparation method of the powder sample comprises sequentially crushing, wet grinding, filtering, concentrating and drying, and the particle size of the powder sample is d 97 <70μm; Conducting chemical composition analysis, phase composition analysis and crystal structure analysis on the powder sample; The optical slices were subjected to electron probe microanalysis, laser Raman spectroscopy, petrography and inclusion microscopy.

2. The quartz ore process mineralogical analysis method according to claim 1, characterized in that: The quartz ore includes one or more of vein quartz ore, granite ore and quartzite ore; Before the sample preparation, the method further includes: selecting quartz ore with specified characteristics as representative quartz ore; and preparing samples of the representative quartz ore; The specified characteristics of the vein quartz ore are: milky white, off-white or white in color, and having an oily luster; The specified characteristics of the granite ore are: light flesh-red, light gray or light white in color, and massive granite with a medium-fine grain structure; The specified characteristics of the quartzite ore are: blocky quartzite with gray or white color.

3. The quartz ore process mineralogical analysis method according to claim 1, characterized in that: The crushing comprises jaw crushing and hammer crushing in sequence; the size of the mineral particles obtained by the jaw crushing is 10-20 mm, and the size of the mineral particles obtained by the hammer crushing is 3-5 mm.

4. The method for process mineralogy analysis of quartz ore according to claim 1, characterized in that: The wet grinding includes sequentially performing wet coarse grinding and wet fine grinding; The particle size of the raw ore slurry obtained by the wet coarse grinding is 97 <300μm; The particle size of the raw ore slurry obtained by wet fine grinding is 97 <70μm.

5. The method for process mineralogy analysis of quartz ore according to claim 4, characterized in that: The grinding medium used in the wet rough grinding is a ceramic ball. The grinding medium of the wet rough grinding includes a first graded grinding medium, a second graded grinding medium and a third graded grinding medium. The particle size of the first graded grinding medium is 10 to 20 mm, the particle size of the second graded grinding medium is 25 to 35 mm, the particle size of the third graded grinding medium is 40 to 50 mm, the mass ratio of the first graded grinding medium, the second graded grinding medium and the third graded grinding medium is (1 to 3): (6 to 8): (1 to 2), and the ball-to-material ratio of the wet rough grinding is 4:1 to 5:1; the rotation speed of the wet rough grinding is 800 to 2000 r / min, and the time is 20 to 45 min; the solid content of the wet rough grinding is 30 to 40 wt.%.

6. The method for process mineralogy analysis of quartz ore according to claim 4, characterized in that: The grinding media used in the wet fine grinding are ceramic balls. The grinding media of the wet fine grinding include first-graded grinding media and second-graded grinding media. The particle size of the first-graded grinding media is 2-4 mm, the particle size of the second-graded grinding media is 5-6 mm, the mass ratio of the first-graded grinding media to the second-graded grinding media is (3-6):1, and the ball-to-material ratio of the wet fine grinding is 4:1-5:1; the rotation speed of the wet fine grinding is 1500-2500 r / min, and the time is 20-30 min; the solid content of the wet fine grinding is 20-30wt.%.

7. The method for process mineralogy analysis of quartz ore according to claim 1, characterized in that: The solid content of the raw ore slurry obtained by filtration and concentration is 65-75wt.%.

8. The method for process mineralogy analysis of quartz ore according to claim 1, characterized in that: The drying is spray drying, the temperature of the spray drying is 100-150° C., and the feed pressure of the spray drying is 0.1-0.2 MPa.

9. The method for process mineralogy analysis of quartz ore according to claim 1, characterized in that: The chemical composition analysis includes: using an X-ray fluorescence spectrometer to determine the element content in the ore powder sample; using an inductively coupled plasma mass spectrometer to determine the type and content of the metal elements in the ore powder sample; using a potassium fluorosilicate volumetric method to determine the SiO2 content in the ore powder sample; The phase composition analysis and the crystal structure analysis are performed using an X-ray diffractometer.

10. A method for determining whether quartz ore can be used as high-purity quartz ore, characterized in that: The following steps are involved: Analyze the quartz ore according to the process mineralogy analysis method according to any one of claims 1 to 9 to obtain five classification indicators of the quartz ore, wherein the five classification indicators include SiO2 content, embedded particle size, gangue mineral type, inclusion characteristics and lattice impurities; When at least three of the five classification indicators of the quartz ore reach Grade A or above, the quartz ore can be used as high-purity quartz ore.

Citation Information

Cited By

  • Purification method of pegmatite high-purity quartz and extraction purity evaluation method

    CN120757120A

  • A pegmatite high-purity quartz purification method and purity evaluation method

    CN120757120B